Optimal reasoning of goals in the i* framework - Subramanian, C.; Krishna, Aneesh; Kaur, Arshinder (2015)
© 2015 IEEE.Requirement analysis involves elicitation of suitable functions or operations and relevant data to support software. A requirement analyst examines different alternative options to decide on an optimal alternative option that benefits the stakeholders of the system. The decision making of alternative design option is complicated by the unavailable or incomplete and imprecise input data. Optimisation, an operation research technique, can be used as a method to solve this problem. The goal-oriented framework, such as i* is used to present social models for the analysis of a software system during the early phase of the requirement's engineering process. This paper aims to develop an optimisation model for the i* goal models, using multi-objective optimisation. The optimisation model aims to fully automate the goal analysis and to handle large goal models. A simulation for the proposed approach was developed by integrating Visual C++ with Matlab and was evaluated with case studies from the existing literature. The evaluation results show that the proposed approach is feasible and offers guidance in the decision making of alternative options.